Z-palatopharyngoplasty combined with 70-degree endoscopy-assisted coblator partial medial glossectomy on severe obstructive sleep apnea. (3rd October 2019) - Chen, Huaihong; Wang, Jiangping; Huang, Xiaoxing; Huang, Yuanshou; Lu, Juan; Li, Xiangping
Abstract: Background: Patients with severe obstructive sleep apnea (OSA) require safe and effective surgical treatment. Objectives: To evaluate the effectiveness of combined Z-palatopharyngoplasty (ZPPP) and partial glossectomy via 70-degree endoscopy-assisted coblation (Eco-TBR) on severe OSA. Materials and methods: Twenty-two consecutive patients with severe OSA were enrolled between September 2014 and July 2016. The lingual artery was evaluated by contrasted computed tomography (CT). Drug-induced sleep endoscopy (DISE) was performed to determine the necessity of multilevel surgery. Combined ZPPP and Eco-TBR were performed. Polysomnographic parameters were collected pre-operatively and 6 months post-operatively. Results: No adverse events were observed postoperatively. The short-term ( < 12 months) rate of total surgical effectiveness was 63.6% (14/22), with Friedman classifications as follows: I (1/1), Friedman II (6/10) and Friedman III (7/11). There were no differences between Friedman classification groups. The differences in AHI, apnea index (AI), mean blood oxygen, and percentage of cumulative time with oxygen saturation < 90% (CT 90%) were different compared to preoperative levels. Tonsil size was also significantly larger in the multi-level surgery group (2.14 ± 1.03) compared with the control group (1.13 ± 0.64). Conclusions and significance: Combined ZPPP and Eco-TB is safe and effective, with good surgical effectiveness for the treatment of severe OSA patients. Trial registration: Chinese Clinical Trial Registry identifier: ChiCTR-CCC-13003415.